CAESAREAN SECTION – INSTRUCTION, EMERGENCY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Caesarean section (lat. sectio caesarea, sectio — "cut" and caedo — "I cut"), Russian. cesarean section is an artificial delivery operation in which the fetus and placenta are removed from the anterior abdominal wall and uterine body. Cesarean section is performed while the fetus is still alive, if the woman cannot give birth on her own (narrow or deformed pelvis, sharp scar changes of the vagina, transversal placenta). In case of profuse and acute bleeding, it is performed to save the life of the mother, even if there is a lifeless or non-viable fetus.